Gasdermins and their role in immunity and inflammation - Orning, Pontus; Lien, Egil; Fitzgerald, Katherine A. (The Journal of experimental medicine, 2019)
The gasdermins are a family of pore-forming proteins recently implicated in the immune response. One of these proteins, gasdermin D (GSDMD), has been identified as the executioner of pyroptosis, an inflammatory form of lytic cell death that is induced upon formation of caspase-1–activating inflammasomes. The related proteins GSDME and GSDMA have also been implicated in autoimmune diseases and certain cancers. Most gasdermin proteins are believed to have pore-forming capabilities. The best-studied member, GSDMD, controls the release of the proinflammatory cytokines IL-1ß and IL-18 and pyroptotic cell death. Because of its potential as a driver of inflammation in septic shock and autoimmune diseases, GSDMD represents an attractive drug target. In this review, we discuss the gasdermin proteins with particular emphasis on GSDMD and its mechanism of action and biological significance.